Pelaksanaan Kegiatan Literasi Pendidikan Pancasila dan Kewarganegaraan di SDN 173455 Sijamapolang melalui Program Kampus Mengajar Angkatan 3 - Abel Holong Andriel Simorangkir; Kondios Mei Darlin Pasaribu; Lukman Pardede; Dian Nirwana Harahap; Henri Rotnedi Pardede (Prima Abdika : Jurnal Pengabdian Masyarakat, 2022)
The Teaching Campus Program is one form of the implementation of the Independent Learning Campus Merdeka (MBKM) in the form of teaching assistance to empower students in helping the learning process in elementary schools in various villages/cities, one of which is SDN 173455 Sijamapolang, kab. Humbang Hasundutan, North Sumatra. In this program, the students involved have the responsibility to assist the school in the teaching process, assist in adapting technology, and assisting school administration. In addition, students have a responsibility to improve literacy and numeracy, especially during a pandemic where education in Indonesia can be considered backward and must be pursued to advance it again.